Proceedings of the 50th International Academic Conference, Paris 2019
DOI: 10.20472/iac.2019.050.019
|View full text |Cite
|
Sign up to set email alerts
|

Yes, We Can! - Palestinian-Israeli Teachers in Jewish-Israeli Schools

Abstract: The goal of the study is to gain a better understanding of the experiences of Palestinian-Israeli minority teachers when teaching at majority state Hebrew secular schools in Israel. Specifically, the objective is to describe and analyze the role of the teachers' work-related experiences in shaping their sense of self-efficacy, job satisfaction, the acculturation process, and how all these affect their feelings regarding their potential role in helping break down stereotypes and misconceptions about the Palesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, most of them claimed to feel strong emotional closeness with the other teacher, a finding that corroborates previous studies about Arab teachers in Jewish schools pointing to positive feelings and attitudes among Arab teachers toward their Jewish colleagues and workplace (Gilat et al. , 2020; Jayusi and Bekerman, 2019). This is not to say, however, that all Arab teachers feel high levels of satisfaction in Jewish schools.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, most of them claimed to feel strong emotional closeness with the other teacher, a finding that corroborates previous studies about Arab teachers in Jewish schools pointing to positive feelings and attitudes among Arab teachers toward their Jewish colleagues and workplace (Gilat et al. , 2020; Jayusi and Bekerman, 2019). This is not to say, however, that all Arab teachers feel high levels of satisfaction in Jewish schools.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Arab teachers in Jewish schools in other studies were found to be highly satisfied with their integration into the school (Bendes-Jacob and Mahool, 2013) and with their working relationship with principals, staff, students and parents (Jayusi and Bekerman, 2019). They felt they were reducing students' prejudice against Arab people as well as contributing to coexistence between Jews and Arabs.…”
Section: Theoretical Frameworkmentioning
confidence: 86%
“…Fourth, educational and psychological research typically focuses on a single case or country. This evidence suggests that peace education (Bar-Tal and Rosen, 2017), through teachers (Jayusi and Bekerman, 2020), classrooms (Pace and Hemmings, 2007) or desegregated schools (Teeger, 2015), may increase prosocial behaviour (Aber et al, 2017), change children's attitudes towards conflict rivals (Burde et al, 2017) or address structural injustice in stable democracies (Holland, 2012). Yet, cross-cultural research is needed.…”
Section: Rapid Evidence Assessmentmentioning
confidence: 99%